Biochemical and molecular characterization of phosphate-solubilizing bacteria isolated from oil palm soil - Javadi, Mohammad Bagher (2012)
Bacterial isolates from Malaysian oil palm soils were examined and screened for capability to solubilize calcium phosphate. In the present study, Pikovskaya (PVK) and NBRIP were chosen as the media for isolating the PSB from different Malaysian oil palm soils. Isolated bacteria were able to solubilize calcium phosphate. The phosphate solubilization ability and microbial growth were dependent on the species of bacteria. The results indicated that maximum solubilization was found up to 7.56 ppm and related to 35dr (S. marcescens). The bacterial isolates exhibited different level of phosphate solubilization when the media containing different carbon or nitrogen sources. 10upmr and 7sr bacterial isolates could solubilize insoluble phosphate with all carbon sources. In all cases, insoluble phosphate solubilization was accompanied by decreasing the pH value. All bacteria isolated were identified using 16S rRNA molecular technique except 32dr, a bacterial isolate which was isolated from Dengkil rhizosphere. The identification analysis confirmed Proteobacteria as the most abundant group in Malaysian oil palm soils. The comparison of the 16S rRNA gene sequences of phosphate solubilizing bacteria allowed differentiation between isolates at the species level across Proteobacteria and Firmicutes phylum but it couldn’t classify isolates at strain. The desired experimental resolution for the differentiation of closely-related isolates of Proteobacteria and Firmicutes phylum was achieved by using the Rep-PCR techniques. With this approach, the polymorphism of 31 PSB from different area were observed. In the case of the PSB isolates examined here, cluster analysis of Pseudomonas and Alcaligenes species could reveal better differentiation by BOXPCR and REP-PCR primers respectively. By using NBRIP media, 16S rDNA and Rep-PCR technique found a very fast and precise method for evaluating Phosphate solubilizing ability, finding the most effective isolates for conducting the molecular process required for creating the strain-base biofertilizer.